The Building of Environmental Geographic Information System for Supporting Environmental Policymaking in Korea - Minki Bae; Deokho Cho; HongSuk Um; Dongho Shin (European Regional Science Association (ERSA), 2004)
The goal of this study is to build a geographic information system for environmental policymaking. To achieve this goal, this study first surveys the local environment status. Based upon the collected environmental data, it forecasts the future environmental status of each city in Gyeongbuk province and generates a geo-referencing code. Finally, by using these data, it builds up a future environmental geographic information system for supporting environmental policymaking. This study consists of three major parts: 1) developing integrated environmental indicators, 2) establishing an environmental capacity database on the local level, 3) building up an environmental capacity geographic information system, and 4) making an environmental policy monitoring system. The results of this study will contribute to establish a warning system to prevent an excess of environmental capacity. They will also provide the framework and standard for integrating various environmental databases with a local environmental and geographic information system. Key words: Environmental indicators, geographic information system, geo-coding and geo-referencing, environmental policy
Keywords: 330; Environmental indicators; geographic information system; geo-coding and geo-referencing; environmental policy